Puncak Penanaman Mangrove Nasional Secara Serentak Jajaran TNI di Seluruh Indonesia oleh Presiden RI - Moch. Nurdin (Akademi Maritim Nusantara Banjarmasin, 2023)
AbstractThe planting in question is a way or process of instilling an action so that what is desired to be instilled will grow in apersonsuch as planting mengrove as one of the mangrove forests or commonly called mangrove forests, even though the mention ofmangrove forests is not really appropriate because mangroves are only one of the mangrove species itself is the type of Rhizoporaspp. Research has shown that the carbon storage capacity of mangroves varies widely, depending on the influence of ecologicalfactors. Scientists have also measured the blue carbon storage capacity of mangrove ecosystems that are affected by changesin land use over time, where there are selective logging and aquaculture activities.Secretariat activities carried out by the ranks of the TNI and other national elements from elements of the IndonesianNational Police, Regional Governments and communities throughout Indonesia led by the President of the Republic ofIndonesia. On May 15 2023, this activity was also attended by the Director of the Banjarmasin ArchipelagoMaritimeAcademy together with cadets as a form of concern and community service for the environment, one of which is plantingmangroves. Located in Taboneo, Tanah Laut Regency. Tanah Laut The Indonesian Navy Base (Lanal) Banjarmasincarried out the planting of Mangrove trees.Keywords: Plating, Mangrove, National